PENGARUH GAME BISIK BERANTAI TERHADAP KETERAMPILAN MENYIMAK SISWA MTS PP AL-WASHLIYAH TANJUNG HALOBAN - Sahidin Ritonga; Zikra Wahyuni Maiza (JURNAL ILMIAH PENELITIAN MAHASISWA, 2023)
Abstract. The research was based on the fact that students were less able to understand the lesson material presented by the teacher so that student learning outcomes were not as expected. The aim of this research is to obtain information regarding improving student learning outcomes regarding listening skills by using the chain whisper game method in learning Arabic. The method used in this research is experimental, with the form of pretest and posttest research used to determine the effect of treatment on research subjects. The population of this study was all 8 classes of Mts Al-Washliyah Tanjung Haloban, with a sample of two classes. Data from the results of this research were obtained using an instrument in the form of student learning scores from their supporting teachers during prerest before the learning process was carried out, posttest which was carried out after the learning process. From the research results, the average pretest value was 64.3 and the average posttest value was 81.35. From the results of this data, researchers can conclude that the learning method using the chain whisper game has a very big influence.